Horn von Afrika, Äthiopien/Eritrea: Migrationsprozesse am nördlichen Horn von Afrika im frühen 1. Jahrtausend v. Chr. - Gerlach, Iris (e-Forschungsberichte des DAI, 2023)
The Orient Department’s Sana‘a Branch is currently examining the migration movement of South Arabian groups of peoples to the northern Horn of Africa during the early 1st millennium BC. At this time, culture-related remains of South Arabian, in particular Sabaean, character emerged in the area of southeast Eritrea and the north of Ethiopia, leading to a cultural change in this region. This transformation process becomes evident in sectors of the political, social and religious life. The project is pursued within the larger context of the DAI cluster “Connecting Cultures”.